Acceptance of technology by parent fraternity as a means of remote learning for children: An empirical study - V K, Gokuladas; Manickam, Sivakumar (International Journal of Educational Technology and Learning, 2023)
The main purpose of this empirical study is to understand how acceptance of technology is prevailing among the parent fraternity that helps them to develop a positive attitude towards using technology as a tool to enhance their ward’s learning process. A survey among 6361 parents (Indian origin) of primary school students (Kindergarten and primary level) regarding their perceived usefulness and perceived ease of use regarding technology-assisted learning for their wards to understand how these factors influence their attitude towards technology for learning in the future was carried out through an online questionnaire. The result showed that the more parents found the Usage of Technology towards the e-learning process of their wards, the higher they tend to adopt the technology by exhibiting a positive Attitude towards Technology while the perception of Ease of Use of Technology also significantly predicted the perception of Attitude towards Technology. The favourable Attitude towards Technology is more visible among the parents of students who are of lower levels of study as compared to those who are at a slightly higher level of study. It is found that the parents of the student from the rural area schools possessed positive Attitudes towards Technology as compared to their counterparts in the urban areas. The outcome of this study is of greater relevance to the schools especially in the lower level classes to help students to harness technology from a young age because the parent fraternity is already in favour of such initiative.